Science-based assurance of the disease freedom in reindeer herds of the Russian Arctic zone - K. A. Laishev; A. A. Yuzhakov (Ветеринария сегодня)
Reindeer husbandry takes a leading position in the agricultural sector of the Russian Federation Arctic zone. The purpose of the research is to analyze the science-based assurance of the freedom from highly dangerous infectious diseases in reindeer herds of the Arctic zone. It has been established that diseases such as anthrax, brucellosis, footrot, rabies are still relevant for the reindeer husbandry and can cause not only significant economic damage, but also diseases in humans. The analysis of the archival data and literary sources, as well as own research data lead to the following conclusions: the greatest risk of anthrax occurrence and spread is posed by old carcass sites; to eradicate brucellosis, vaccination of animals along with the general disease control measures is necessary; in case of footrot, special attention should be paid to the control of blood-sucking insects and warble flies; to prevent rabies in reindeer herds, it is important to avoid contacts between deer and wild carnivores and consider emergency vaccination. Undoubtedly, the eradication and prevention of the above-mentioned infectious diseases requires constant epidemiological surveillance, including its element – monitoring, with all necessary special management, animal health measures. There is an obvious need for constant surveillance of infectious diseases in the Arctic zone of the Russian Federation using GIS technologies. It is important to pay special attention to the generation of special information layers related to disease characteristics, including deer herd migration routes, sites where anthrax outbreaks were recorded, and the location of disease-infected facilities.